Hamilton Harbour over the last 25 years: Insights from a long-term comprehensive water quality monitoring program. Issue 2 (2nd April 2016) - Hiriart-Baer, V. P.; Boyd, D.; Long, T.; Charlton, M. N.; Milne, J. E.
Abstract : Hamilton Harbour was identified by the International Joint Commission as a problem area in 1978 and later identified as an Area of Concern in 1985. In response to its Remedial Action Plan, the harbour has been systematically monitored since 1987. In this study, we present the long-term water quality record (1987 to 2012) of Hamilton Harbour, focusing on the parameters and seasonal intervals of particular importance to the Remedial Action Plan beneficial use impairments. The long-term summer records showed that total phosphorus concentrations decreased in the first decade and have remained relatively unchanged since 1998, while an increasing trend in Secchi disc depth was observed until 2005 only to be reversed since then. No significant changes in chlorophyll a concentrations have been observed since 1987 despite significant changes in total phosphorus. Hypoxia in the hypolimnion of Hamilton Harbour remains a common occurrence and despite long-term trend improvements there has been little change over the last decade. Spring conditions have also changed, and higher conductivity values and chlorophyll a concentrations have been measured in recent years. A strong correlation between spring hypolimnetic dissolved organic carbon concentrations and dissolved oxygen depletion rates was found suggesting the organic material load to the harbour is an important controlling factor for hypoxia. Finally, the data suggest that the hypolimnetic accumulation rate of soluble reactive phosphorus in the summer has increased since 1987, most notably since the early 2000s. However, it is only since 2008 that this translated into an increasing trend in hypolimnetic soluble reactive phosphorus concentrations. These data suggest that conditions have recently changed in Hamilton Harbour and that sediment phosphorus release may delay water quality improvements for many years following reductions in total phosphorus loadings. Further research is needed to understand the implications to the Remedial Action Plan water quality goals.